THE ROLE OF ULTRASOUND AND VIDEOLAPAROSCOPY IN DIAGNOSIS AND TREATMENT OF ACUTE SURGICAL DISEASES OF THE ABDOMINAL CAVITY ORGANS IN CHILDREN - SH.R. SULTONOV; S.S. RASULOV; M.F. ABDULLOEV; KH.D. GURIEV (Avicenna Tajik State Medical University, 2018)
Objective: To improve the results of diagnostic and treatment of acute surgical diseases of organs of the abdominal cavity (ASDOAC) in children. Methods: The work is based on the study of 327 seek children with different ASDOAC at the age of 2 to 15 years. The boys were 125 (38.2%), girls - 202 (61.8%). The ASDOAC included: acute appendicitis and its complications - 163 (49.9%), pathology of pelvic organs - 139 (42.5%), intussusception - 14 (4.2%) and pathology of Meckel's diverticulum - 11 (3.3%) of cases, of which in 5 - Meckel's diverticulum was the cause of acute intestinal obstruction. Results: Suggested therapeutic and diagnostic tactics for ASDOAC in children with the extensive use of ultrasound and video laparoscopy is rational and very effective. Sensitivity and specificity of ultrasound in the diagnosis of ASDOAC was more than 92%. Video laparoscopy is also a highly informative, relatively safe and objective method for diagnosing ASDOAC in children and in 100% of cases, it allows to clarify the diagnosis and choose the optimal tactics for surgical treatment. Conclusion: Comparative analysis of diagnosis and treatment of ASDOAC convincingly proves that traditional methods are much inferior to video-laparoscopic operations on the severity of the operating period, the number of postoperative complications, the normalization of clinical and laboratory parameters, the reduction in hospitalization of patients, and cosmetic results, especially in girls.